2020
DOI: 10.7554/elife.54566
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ entry through NaV channels generates submillisecond axonal Ca2+ signaling

Abstract: Calcium ions (Ca2+) are essential for many cellular signaling mechanisms and enter the cytosol mostly through voltage-gated calcium channels. Here, using high-speed Ca2+ imaging up to 20 kHz in the rat layer five pyramidal neuron axon we found that activity-dependent intracellular calcium concentration ([Ca2+]i) in the axonal initial segment was only partially dependent on voltage-gated calcium channels. Instead, [Ca2+]i changes were sensitive to the specific voltage-gated sodium (NaV) channel blocker tetrodot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 93 publications
(169 reference statements)
14
55
1
Order By: Relevance
“…Furthermore, we found that the kinetics of sodium and calcium influx were indeed identical, but that calcium influx lagged sodium influx in ways that were consistent with sodium and calcium influx occurring on the rising and falling phases of the AP, respectively. These results are consistent with studies using highspeed optical imaging, where sodium influx occurs during the rising phase of the AP (Filipis and Canepari, 2020), whereas calcium influx occurs during the falling phase of the AP in the AIS or AIS-like regions of AP initiation (Hanemaaijer et al, 2020;Pressler and Strowbridge, 2019). Furthermore, we observed consistent results at both room temperature and physiological temperatures with two different sodium-sensitive indicators and two different calcium-sensitive indicators, suggesting that calcium influx occurs during CaV-mediated tail currents on the falling phase of the AP in the axon, regardless of temperature (Kawaguchi and Sakaba, 2015;Pressler and Strowbridge, 2019;Rowan et al, 2014;Sabatini and Regehr, 1996).…”
Section: Activity-dependent Calcium Sources In the Aissupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, we found that the kinetics of sodium and calcium influx were indeed identical, but that calcium influx lagged sodium influx in ways that were consistent with sodium and calcium influx occurring on the rising and falling phases of the AP, respectively. These results are consistent with studies using highspeed optical imaging, where sodium influx occurs during the rising phase of the AP (Filipis and Canepari, 2020), whereas calcium influx occurs during the falling phase of the AP in the AIS or AIS-like regions of AP initiation (Hanemaaijer et al, 2020;Pressler and Strowbridge, 2019). Furthermore, we observed consistent results at both room temperature and physiological temperatures with two different sodium-sensitive indicators and two different calcium-sensitive indicators, suggesting that calcium influx occurs during CaV-mediated tail currents on the falling phase of the AP in the axon, regardless of temperature (Kawaguchi and Sakaba, 2015;Pressler and Strowbridge, 2019;Rowan et al, 2014;Sabatini and Regehr, 1996).…”
Section: Activity-dependent Calcium Sources In the Aissupporting
confidence: 91%
“…While action potential-evoked Ca V -mediated calcium influx has been observed in the AIS of a range of cell classes, the channels that mediate such influx appear to vary from class to class (Bender and Trussell, 2009; Clarkson et al, 2017; Hanemaaijer et al, 2020; Martinello et al, 2015; Yu et al, 2010). To determine the relative contributions of different calcium channel types during AP-evoked calcium influx in mouse prefrontal pyramidal cells, we made whole-cell current-clamp recordings from layer 5 pyramidal neurons in slices prepared from mice aged 20-30 days old.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations